Pengaruh Aplikasi Android Aneminfo terhadap Pengetahuan dan Sikap Remaja Putri terkait Anemia Defisiensi Besi - Rizki Septia Saraswati; Apoina Kartini; Farid Agushybana (Jurnal Promosi Kesehatan Indonesia, 2020)
Background: Iron deficiency anemia is one of the nutritional problems that still occur in Indonesia which is common in young women. Early nutrition education is needed to prevent these problems. The purpose of this study was to analyze the effect of the android-based educational media "Aneminfo" on the knowledge and attitudes of young women regarding iron deficiency anemia. Method: This research was conducted with a quasi-experimental design with a pre-post control group design with a sample of 37 people for each group taken from 2 vocational schools in the city of Semarang. The intervention was carried out using educational media in the form of the “Aneminfo” android application. Changes in knowledge and attitudes between before and after the intervention were measured using a validated questionnaire and tested using the Wilcoxon and Mann-Whitney tests. Results: The results showed a significant increase in knowledge in the intervention group (p = 0.001), and there was a significant increase in attitude in the intervention group (p = 0.011) compared to the control group. The conclusion of this study is the Aneminfo android application can be an alternative media for the government and health workers in providing education about iron deficiency anemia to increase adolescent knowledge and prevent anemia from an early age.